THE EFFECTIVENESS OF USING LONTARAQ CARD MEDIA IN LEARNING TO READ BUGIS LANGUAGE TEXTS FOR CLASS III STUDENTS OF SD NEGERI 51 TONRONGE SOPPENG DISTRICT - Sahriani, Sahriani; Amir, Johar; Asri, Aswati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This research aims to determine the effectiveness of using Lontaraq card media in learning to read Bugis language texts for class III students at SDN 51 Tonronge, Soppeng Regency. This type of research is quantitative research in the form of an experiment. The research design used was One Group Pretest-Posttest, which was carried out at SDN 51 Tonronge. The data collection technique used is the test technique. The data analysis techniques are normality test, homogeneity test, and hypothesis test (t-test). The results of the hypothesis test analysis (paired sample test) show that the t-value = 17,964 > t-table value = 2,160 (n = 14) with a significance of 0.025. Thus, H1 is accepted and H0 is rejected. It can be concluded that the Lontaraq card learning media is effectively used in learning to read Bugis language texts for class III students at SD Negeri 51 Tonronge.